Melatonin alleviates high temperature exposure induced fetal growth restriction via the gut-placenta-fetus axis in pregnant mice - Jia-Jin Wu; Xiaoyu Zheng; Caichi Wu; Wen Ma; Yibo Wang; Jun Wang; Yulong Wei; Xiangfang Zeng; Shihai Zhang; Wutai Guan; Fang Chen (Journal of Advanced Research)
Introduction: Global warming augments the risk of adverse pregnancy outcomes in vulnerable expectant mothers. Pioneering investigations into heat stress (HS) have predominantly centered on its direct impact on reproductive functions, while the potential roles of gut microbiota, despite its significant influence on distant tissues, remain largely unexplored. Our understanding of deleterious mechanisms of HS and the development of effective intervention strategies to mitigate the detrimental impacts are still limited. Objectives: In this study, we aimed to explore the mechanisms by which melatonin targets gut microbes to alleviate HS-induced reproductive impairment. Methods: We firstly evaluated the alleviating effects of melatonin supplementation on HS-induced reproductive disorder in pregnant mice. Microbial elimination and fecal microbiota transplantation (FMT) experiments were then conducted to confirm the efficacy of melatonin through regulating gut microbiota. Finally, a lipopolysaccharide (LPS)-challenged experiment was performed to verify the mechanism by which melatonin alleviates HS-induced reproductive impairment. Results: Melatonin supplementation reinstated gut microbiota in heat stressed pregnant mice, reducing LPS-producing bacteria (Aliivibrio) and increasing beneficial butyrate-producing microflora (Butyricimonas). This restoration corresponded to decreased LPS along the maternal gut-placenta-fetus axis, accompanied by enhanced intestinal and placental barrier integrity, safeguarding fetuses from oxidative stress and inflammation, and ultimately improving fetal weight. Further pseudo-sterile and fecal microbiota transplantation trials confirmed that the protective effect of melatonin on fetal intrauterine growth under HS was partially dependent on gut microbiota. In LPS-challenged pregnant mice, melatonin administration mitigated placental barrier injury and abnormal angiogenesis via the inactivation of the TLR4/MAPK/VEGF signaling pathway, ultimately leading to enhanced nutrient transportation in the placenta and thereby improving the fetal weight. Conclusion: Melatonin alleviates HS-induced low fetal weight during pregnancy via the gut-placenta-fetus axis, the first time highlighting the gut microbiota as a novel intervention target to mitigate the detrimental impact of global temperature rise on vulnerable populations.